COST INFORMATION AND ENERGY EFFICIENCY: EXPERIMENTAL STUDY ON IN THE DESIGN OF NEW SUSTAINABLE PRODUCTS - Fadilla Damara Putri; Dyah Ekaari Sekar Jatiningsih (RADJA PUBLIKA, 2025)
This study explores the influence of cost information and energy efficiency in sustainable new product development. With a 2x2 factorial experimental design, the study involved Accounting students of Universitas Muhammadiyah Yogyakarta. Data were collected through experimental tasks based on the type of cost information and the level of energy efficiency. The ANOVA results showed that energy efficiency had a significant effect on green product design, while cost information had no direct effect. These findings emphasize the importance of energy efficiency in product development for sustainability. Green products can reduce production costs, minimize waste, and increase competitiveness. The application of green technology also attracts investment, creates jobs, and supports industrial innovation. In addition, compliance with environmental regulations strengthens sustainable economic growth and improves people's quality of life. Thus, this study contributes to encouraging business practices that support sustainability and industrial innovation.